Investigation of rheological synergistic interactions between hydrocolloids and starch in milky cacao beverages model: principal component analyses - Dogan, Mahmut; Sarac, Meryem Goksel; Toker, Omer Said (SPRINGER, 2017)
In this study, effects of different selected starches (tapioca, potato, modified corn) and gums (xanthan gum, guar gum, locust bean gum) on the rheological behaviour of model milky cacao beverages were studied for improvement in the rheological properties of milky cacao beverages which directly affect consumer acceptability of the product. The soluble solids, pH and colour values of the samples were also determined. Milky cacao beverages showed pseudoplastic behaviour. Ostwald de Waele model accurately described the flow behaviour of all beverage samples with high R-2 values very close to unity. K (consistency coefficient), and n (flow behaviour index) values were found to between 5.5-170.64 mPa s, 0.387-0.999, respectively. Principal component analysis was successfully performed to classify the milky cacao beverages including different starch and gum combinations. The results of the present study highlighted that selection of optimum starch and gum combination is very important for production of the product with desired quality.
Keywords: Milky cacao beverages; Starch; Gum; Rheology; PCA; HOT CHOCOLATE BEVERAGE; MIXTURE DESIGN APPROACH; RICE STARCH; GUAR GUM; GALACTOMANNANS; OPTIMIZATION; COMBINATION; POTATO; Food Science & Technology